Gopal Datt Bhatta shares experiences on Participatory Video Documentation in South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Gopal Datt Bhatta, Science Officer- CGIAR Research program on Climate Change, Agriculture and Food Security (CCAFS) shares experiences on Participatory Video Documentation in South Asia Video by Meerim Shakirova, social media reporter